POTENSI MIKROBA ASAL MIKROORGANIME LOKAL DALAM MENINGKATKAN PERKECAMBAHAN BENIH PAPRIKA - Abdul Hasyim Sodiq; Mieke Rochimi Setiawati; Dwi Andreas Santosa; Dedi Widayat (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTThis experiment was continues from the study of biological fertilizers potential’slocal microorganisms from the best main raw materials obtained from previousexperiments. This experiment used five selected raw materials to make localmicroorganisms, including: bamboo roots, broccoli leaves, chicken manure, rabbit manure and goat manure, each raw material was made 2 times so that there were 10 local microorganisms samples. The results showed that the highest of total bacterial population were shown by local microorganisms goat manure with a value of 7.2 x 105 cfu/ml, then the highest population of Azotobacter and Azospirillium were shown by local microorganisms rabbit manure with values of 6.4 x 104 cfu/ml and 3.5 x 103 cfu/ml and total fungi populations was local microorganisms goat manure with a value of 4.7 x 103 propagules/ml. In the pathogenicity test, 9 nine bacterial isolates were obtained, 25 Azotobacter isolates, 15 Azospirillium isolates were proven to provide negative responses to the pathogenicity test. Furthermore, in the seed nurserytest, only 33 microbial isolates were obtained which could support the growth ofpaprika seeds with the best results were shown by aquadest water control, 4B-1 NFB, 5A-1 NFB, and 1A-2 NFB isolates respectively.